Study on the Influence Mechanism of Virtual Simulation Game Learning Experience on Student Engagement and Entrepreneurial Skill Development - Yang, Qixing; Zhang, Yue; Lin, Yawen (Frontiers in Psychology, 2022)
With the emergence of the COVID-19 pandemic, virtual simulation games have provided an effective teaching method for online entrepreneurship education. By exploring the mechanisms that influence student engagement and learning outcomes from different perspectives, such as game design, team and individual perspectives, numerous scholars have demonstrated that such a teaching method can effectively improve students' engagement and learning performance. However, the existing studies are relatively scattered, and there is a scarcity of studies in which the effects of said factors are considered. Based on the learning process 3P model (presage-process-product) proposed by Biggs (1993), students' perceived experience of game design, teamwork and self-efficacy were taken as variables in the early learning stage in the present study, and the influence mechanism of virtual simulation game learning experience on students' engagement and entrepreneurial skill development was explored, so as to close the gap in existing research. In the present study, 177 college students from Chinese universities were surveyed and the data were surveyed using AMOS 23.0 software. Although the empirical results show that students' "goal and feedback" and "alternative" experience of game design did not have a significant positive impact on students' engagement, there was a direct and significant effect the development of entrepreneurial skills. Students' experience of teamwork and general self-efficacy could not only directly and significantly affect the development of entrepreneurial skills, but also indirectly affect the development of entrepreneurial skills through learning engagement. The research results are practically significant for teachers in the selection and development of virtual simulation games, can be effectively applied in teaching process management, and can improve students' engagement and learning performance.